2005
DOI: 10.1590/s0074-02762005000300012
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi isolates from Mexican and Guatemalan acute and chronic chagasic cardiopathy patients belong to Trypanosoma cruzi I

Abstract: Trypanosoma cruzi is classified into two major groups named T. cruzi I and T. cruzi II. In the present work we analyzed 16 stocks isolated from human cases and four isolated from triatomines from diverse geographical origins (Mexico and Guatemala). From human cases four were acute cases, six indeterminates, and six from chronic chagasic cardiophatic patients with diagnosis of dilated cardiomyopathy established based on the left-ventricular end systolic dimension and cardiothoracic ratio on chest X-radiography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 9 publications
1
33
1
3
Order By: Relevance
“…The predominance of T. cruzi Lineage I in Mexico is not limited to just marsupials; it has also being found in humans and vectors (Ruíz-Sánchez et al 2005, Gómez-Hernández et al 2011. Our findings contrast with those from South American countries were T. cruzi lineage II is the main genotype associated with human infections (domestic cycle) (Bosseno et al 2002).…”
Section: Resultscontrasting
confidence: 87%
“…The predominance of T. cruzi Lineage I in Mexico is not limited to just marsupials; it has also being found in humans and vectors (Ruíz-Sánchez et al 2005, Gómez-Hernández et al 2011. Our findings contrast with those from South American countries were T. cruzi lineage II is the main genotype associated with human infections (domestic cycle) (Bosseno et al 2002).…”
Section: Resultscontrasting
confidence: 87%
“…In Mexico, most T. cruzi strains have been genetically determined to belong to TcI (Bosseno et al 2002, Leó n-Pérez et al 2007, Gó mez-Hernández et al 2011 and TcII-TcVI strains have been reported only in a recent serological study, in wild mammals and the feces of vectors (Ló pez-Olmos et al 1998, Bosseno et al 2009, Risso et al 2011. In this work, we confirmed that the Mexican T. cruzi strains isolated from humans belonged to TcI, as reported in Guatemala, Colombia, and Venezuela (Añ ez et al 2004, Ruíz-Sánchez et al 2005, Falla et al 2009). In the present work, 2 other strains from wild mammals belonging to TcIITcVI groups were also identified, but their association with any specific DTU remains to be determined.…”
Section: Discussionsupporting
confidence: 85%
“…The following eight T. cruzi strains were studied: three strains isolated from Triatoma pallidipennis (CGH2, CGH4, and CGH6 strains), two from Triatoma longipennis (CGH1 and CGH3 strains), one from Triatoma picturata (KR1 strain), one by xenodiagnosis from a patient in the acute phase of disease (NINOA strain) 21 , and one isolated from a patient with the chronic cardiac form (INC-5 strain) 22 (Table 1).…”
Section: Gómez-hernández C Et Al -Molecular Characterization Of Trypamentioning
confidence: 99%